Ceramide Metabolism in Cardiovascular Disease: A Network With High Therapeutic Potential. Issue 10 (25th August 2022) - Zietzer, Andreas; Düsing, Philip; Reese, Laurine; Nickenig, Georg; Jansen, Felix
Abstract : Growing evidence suggests that ceramides play an important role in the development of atherosclerotic and valvular heart disease. Ceramides are biologically active sphingolipids that are produced by a complex network of enzymes. Lowering cellular and tissue levels of ceramide by inhibiting the ceramide-producing enzymes counteracts atherosclerotic and valvular heart disease development in animal models. In vascular tissues, ceramides are produced in response to hyperglycemia and TNF (tumor necrosis factor)-α signaling and are involved in NO-signaling and inflammation. In humans, elevated blood ceramide levels are associated with cardiovascular events. Furthermore, important cardiovascular risk factors, such as obesity and diabetes, have been linked to ceramide accumulation. This review summarizes the basic mechanisms of how ceramides drive cardiovascular disease locally and links these findings to the intriguing results of human studies on ceramides as biomarkers for cardiovascular events. Moreover, we discuss the current state of interventions to therapeutically influence vascular ceramide metabolism, both locally and systemically.